Remote Ischemic Conditioning With Exercise (RICE)—Rehabilitative Strategy in Patients With Acute Ischemic Stroke: Rationale, Design, and Protocol for a Randomized Controlled Study - Han, Zhenzhen; Zhao, Wenbo; Lee, Hangil; Wills, Melissa; Tong, Yanna; Cheng, Zhe; Dai, Qingqing; Li, Xiaohua; Wang, Qingzhu; Geng, Xiaokun; Ji, Xunming; Ding, Yuchuan (Frontiers in Neurology, 2021)
Objective: Exercise rehabilitation is an effective therapy in reducing the disability rate after stroke and should be carried out as early as possible. However, very early rehabilitation exercise exacerbates brain injury and is difficult to conduct in stroke patients due to their weakened and potentially disabled state. It is valuable to explore additional early rehabilitation strategies. Remote Ischemic Conditioning (RIC) is a novel therapy designed to protect vital organs from severe lethal ischemic injury by transient sublethal blood flow to non-vital organs, including the distal limbs, in order to induce endogenous protection. RIC has previously been conducted post-stroke for neuroprotection. However, whether combined early RIC and exercise (RICE) therapy enhances stroke rehabilitation remains to be determined. Methods: This is a single-center, double-blinded, randomized controlled trial that will enroll acute ischemic stroke patients within 24 h of symptom onset or symptom exacerbation. All enrolled patients will be randomly assigned to either the RICE group (exercise with RIC) or the control group (exercise with sham RIC) at a ratio of 1:1, with 20 patients in each group. Both groups will receive RIC or sham RIC within 24 h after stroke onset or symptom exacerbation, once a day, for 14 days. All patients will begin exercise training on the fourth day, twice a day, for 11 days. Their neurological function [Modified Rankin Scale (mRS) score, National Institutes of Health Stroke Scale (NIHSS) score, Barthel Index, and walking ability], infarct volume (nuclear magnetic resonance, MRI), and adverse events will be evaluated at different time points in their post-stroke care. Results: The primary outcome is safety, measured by the incidence of any serious RICE-related adverse events and decreased adverse events during hospitalization. The secondary outcome is a favorable prognosis within 90 days (mRS score < 2), determined by improvements in the mRS score, NIHSS score, Barthel Index, walking ability after 90 days, and infarct volume after 12 ± 2 days. Conclusion: This study is a prospective randomized controlled trial to determine the rehabilitative effect of early RIC followed by exercise on patients with acute ischemic stroke. Trial Registration:www.chictr.org.cn, identifier: ChiCTR2000041042